Features of idiolect in the punctuation of electronic mail - Žalkauskaitė, Gintarė (Lietuvių kalba, 2011)
The article deals with the usage of punctuation marks in the emails of six different authors. Punctuation marks belong to the graphical level of a text, which makes the electronic discourse more distant from standard written language. As a result, a prediction is made that in the electronic communication punctuation marks may be used specifically. The aim of the article is to determine whether punctuation in electronic mail can be linked with the author's idiolect. The corpus of electronic messages under investigation consists of 65,090 words. In total, there are 13,548 punctuation marks used in it. In the present analysis of punctuation, an attempt is made to measure the total number of punctuation marks as well as the number of them as used by each author. In addition the situations in which each punctuation mark is used are also investigated. In the analysis of general tendencies in punctuation mark usage, it has been noted that many different punctuation marks are used in electronic messages. The most numerous marks have proved to be regular ones such as commas, full stops, question marks, dashes, suspension points, brackets, quotation marks, and exclamation marks. The punctuation marks that are used sparingly in traditional written language and electronic communication (various combinations of different punctuation marks, non-traditional variants of punctuation marks, slashes, semicolons) could have the identification value if they were used frequently by any of the authors in their texts.
Keywords: none